CIDADE, TRABALHO E CONSUMO: a experiência dos jovens pobres na contemporaneidade - Maria Aparecida Tardin Cassab (Universidade Federal do Maranhão, 2010)
This paper presents partial results of a research that has as its main intent the discussion of poor youth conditions in Brazilian society today. To do so, after a brief methodological note, we discuss the connections between the experiences of young residents of a medium-sized city in the production of an experience of class position. The concepts and categories of city, work and consumption, are presented as central elements for the discussion proposed because they are essencial parts of the livelihood of poor young people in their ties to their generation.